Determination of mechanical properties of human bone - Parthiban, Sothi (2008)
Human bones are a bioceramic composite material which has very unique properties and structure. The mechanical properties of the bone are to be determined in this project using state-of-the-art finite element model. The geometry of finite element model was constructed in SolidWorks mechanical CAD package. The micron size pores were created using spline-feature-extrude method to include porosity as close as possible to that of the natural bone. The computational domain was determined through trial-meshing by which the model than can be successfully discretized was obtained. Mechanical properties were based on compression type of loading. Essential properties to incorporate into the FE modeling and realistic range of compressive load were obtained from the compression test done with the synthetic specimen. Special fixture was developed for holding very delicate specimen and to eliminate possible errors during the compression test. Compression test was carried out until the bone specimen fractured. The same load range applied in the experiment was defined in the FE model and compression analysis was performed to virtually determine mechanical properties. The FE model was validated by experimentally found mechanical properties. The properties used to validate is the Young’s Modulus. The experimental value of the Young’s modulus is 5202 MPa while the FE analysis gives a value of 5290 MPa. The percentage of error is calculated to be 1.7%. The FEM model is validated as its percentage of error is less than 10%. Hence, the mechanical properties by FEM were found to be Young’s Modulus of 5290 MPa and Poisson ratio of 0.3. The proposed FE model can be used to analyze the response of the human bone under various loading.